Exploring the relevance of outdoor classroom for adaptive Problem Based Learning (PBL) among students in selected Malaysian universities - Rozali, Nur Fadhilah; Mohd. Yaman, Maheran; Abdullah, Fadzidah (IIUM Press, 2017)
This book explores the relevancy of an outdoor classroom for adaptive Problem Based Learning (PBL) approach in Malaysian Higher Institutions. The purpose of this book is to examine the significant criteria of the outdoor classroom in the university campus design and to analyse the relevancy of the outdoor classroom in adapting the PBL approach for students effective learning. Currently, students have limited exposure to learning sessions in outdoor classrooms due to the limitation of the physical environment and cultural context. Students tend to minimise their use of outdoor spaces and utilise indoor classroom more often. This leads to less connectivity between outdoor spaces and indoor classrooms, causes students to create a ‘space barrier’ and limit their learning activities outdoors. This also hinders students to facilitate the usage of outdoor spaces, as the PBL approach encourages students to utilise outdoor classrooms effectively. This study employs both qualitative and quantitative approaches, where a mixed-method of data collection is structured for table research and questionnaire survey. The purpose of the table research is to gather secondary data, to provide in-depth understanding and to further analyse the relationship between campus environment and students’ physical and psychological development. A survey is conducted to examine students’ effective learning with the PBL approach in the outdoor classrooms. For the survey, targeted participants are students from Architecture and Landscape Architecture students in three selected universities; Universiti Islam Antarabangsa Malaysia (UIAM), Universiti Putra Malaysia (UPM), and Universiti Teknologi Mara Kampus Puncak Alam (UiTM). The questionnaire survey has obtained 300 samples, and analyse of the survey are used to determine the statistical relationship between outdoor classrooms with student learning activities and performances, and also to provide a correlation analysis between intervening variables to establish the connections on the physical qualities of an outdoor classroom and student PBL processes.The result of the analysis indicates that the criteria for an outdoor classroom and PBL practices in the studio design-based programme promote positive benefits to student learning performances, as well as increase the positive influence on student personal and social skills. The book then provides recommendations to improve outdoor landscape environment on campus layout that integrate with the PBL approach for future reference.